Impaired adenylate cyclase signaling in acute myocardial ischemia: Impact on effectiveness of P2Y12 receptor antagonists. Issue 181 (September 2019) - Imam, H.; Nguyen, T.H.; De Caterina, R.; Nooney, V.B.; Chong, C.-R.; Horowitz, J.D.; Chirkov, Y.Y.
Abstract: Introduction: P2Y12 receptor antagonists reduce risk of thrombotic complications after stent implantation but increase bleeding risk. Activation of P2Y12 receptors by ADP causes Gi-protein-mediated inhibition of adenylate cyclase (AC), thus limiting platelet response to anti-aggregatory effect of prostacyclin (PGI2 ). However, P2Y12 blockade reverses this ADP-induced suppression of the platelet PGI2 /AC signaling pathway. We previously demonstrated that impairment of this pathway predicts poor response to clopidogrel. Objectives: To identify clinical correlates of variability in PGI2 /AC signaling, and to assess the impact of such variability on individual responses to the direct P2Y12 receptor antagonists ticagrelor ( in vivo ) and 2-methyl-thioadenosine-monophosphate (2MeSAMP) ( in vitro ). Patients/Methods: We compared the inhibitory effects of prostaglandin E1 (PGE1 ) and the PGI2 analog Iloprost (Ilt) on platelet aggregation in whole blood samples from healthy control subjects ( n  = 17), and patients with stable angina pectoris (SAP; n  = 35) or acute coronary syndromes (ACS; n  = 23), with or without associated diabetes/hyperglycemia. Results: Compared to control subjects, patients with ACS and – to a lesser extent – those with SAP, exhibited impaired responses to PGE1, accentuated in the presence of hyperglycemia. Efficacy of ticagrelor treatment, measured as change in platelet reactivity index, was directly related to pre-treatment PGE1 response, both at univariate and multivariate analysis. There was a strong correlation between extent of inhibition of platelet aggregation, whether by PGE1 or Ilt, and the anti-aggregatory effect of 2MeSAMP in vitro . Conclusions: The integrity of PGI2 /AC signaling, which is impaired in the presence of ACS and hyperglycemia, predetermines the anti-aggregatory efficiency of P2Y12 receptor antagonists. Highlights: Prostaglandins E1 and I2 activate adenylate cyclase (AC), thus inhibiting aggregation. P2Y12 receptor antagonists reverse ADP-induced suppression of platelet AC signaling. Both acute coronary syndromes and hyperglycemia impair AC signaling in platelets. Therefore pre-treatment AC signaling efficacy predicts response to ticagrelor therapy. This may facilitate sequential adjustment of P2Y12 antagonist treatment regimens.